ANALISIS JUAL BELI KITAB DENGAN SISTEM ONLINE MENURUT PERSPEKTIF FIKIH MUAMALAH - Henny Dwijayani; Slamet Khusaini (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The objectives of this study are: 1) To find out how the contract mechanism is applied in the book buying and selling transaction using the online system, 2) To find out how the muamalah fiqh view of the book buying and selling transactions using the online system. The result of this research is the practice of buying books with an online system by the santri of Darussalam Blokagung Islamic Boarding School in the view of muamalah fiqh is not at all against the law of fiqh, because in practice it starts from transactions, contracts, objects of transactions, to the two transactors (al- ‘aqidain) did not violate the rules in the muamalah fiqh. This can be seen from the occurrence of the contract, between the buyer and the seller making an agreement in accordance with the provisions of fiqh, then for the perpetrators they are baligh, sensible, have targeted their own assets and there is no element of coercion from any party, the object is in accordance with the law of fiqh. That is, it is not in the form of an unclean object, has benefits, its shape can be clearly identified and the new is already its own.